Reading Motivation and Reading Interests of Pupils in the Final Educational Period (Interdisciplinary Research in Teaching and Learning: New Perspectives and Approaches, 2024)
When it comes to providing motivation for reading, it is important not only to select suitable texts, but also to examine them appropriately at the various levels of school reading: as part of regular literature lessons, required reading, the reading badge or other forms of reading activities. This study focuses on library use and reading of literature in the context of required reading and reading badges among pupils in the final educational period at a selected primary school. The results of the survey will help teachers of the Slovenian language to plan the reading syllabus and motivational reading activities in order to increase interest in literature, and to promote the development of a reading culture.